Estimating narwhal (Monodon monoceros) age using tooth layers and aspartic acid racemization of eye lens nuclei. Issue 1 (3rd June 2019) - Watt, Cortney A.; Stewart, Barbara E.; Loseto, Lisa; Halldorson, Thor; Ferguson, Steven H.
Abstract: Counting growth‐layer groups (GLGs) in teeth is one of the most precise and widely accepted methods for aging marine mammals. Male narwhals have a large erupted tusk that can be used for aging, but this tusk is often difficult or expensive to obtain from hunters and most females do not display the tusk; thus, alternative methods for narwhal aging are needed. In this study, we aged narwhals by counting annual GLGs in embedded tusks and by measuring the change in the ratio of D‐ and L‐enantiomers of aspartic acid in the eye lens nucleus that occurs as the animal ages (the aspartic acid racemization [AAR] technique). Absolute age estimates were estimated for seven tusks aged ≤15 yr. Estimated age was a significant predictor of aspartic acid D/L ratios with a racemization rate ( K asp ) of 9.72 × 10 −4 /year ± 2.28 × 10 −4 and a (D/L)0 of 3.46 × 10 −2 ± 1.78 × 10 −3 ( r 2 = 0.74). Results from our study, which included more younger GLG‐aged animals than previously evaluated, confirms AAR can be used to generate age estimates for narwhals.